Colour Cues: Effects of Ipomoea Plant Extract on Culex quinquefasciatus Say Gravid Females in Choosing Oviposition Site - Wan Fatma Zuharah,; Maniam Thiagaletchumi,; Nik Fadzly, (Tropical Life Sciences Research, 2016)
The interaction between plants and insects is dynamic, and may favour either the plant or the insect. Plant chemicals are deeply implicated in this relationship and influence insect behaviour. Here, we investigated the oviposition behaviour response of Culex quinquefasciatus mosquitoes based on the colour cues produced by Ipomoea cairica leaves extract. In this study, two sets of oviposition choice experiments were conducted: (1) single solution in a cage; and (2) multiple concentration solutions in a cage. In the single solution experiment, only 1 available oviposition site was offered to 5 gravid females and in the multiple concentration tests, 4 available oviposition sites were offered to 20 gravid females. The tested concentrations were set up at 100 mL of: (1) control (distilled water only); (2) 50 ppm; (3) 150 ppm; and (4) 300 ppm of I. cairica plant extracts. The highest concentration of 300 ppm appeared to show the highest intensity with the darkest colour followed by 150 ppm and 50 ppm concentrations. More gravid females were found drowned in the highest concentration, 300 ppm of acethonilic leaves extract, compared to 150 ppm and 50 ppm of the tested extract. No eggs were found in all tested solutions. The studied extract was found to effectively attract gravid Cx. quinquefasciatus females and subsequently cause mortality and inhibit egg deposition. The interference caused by the acethonilic extract of I. cairica on the oviposition activity of Cx. quinquefasciatus can result in better control of the vector insect. Interaksi antara tumbuhan dan serangga adalah dinamik, dan memberikan kebaikan kepada samada tumbuhan ataupun serangga. Bahan kimia tumbuhan adalah terlibat secara mendalam dalam hubungan ini dan mempengaruhi kelakuan serangga. Di sini, kami mengkaji kelakuan tindak balas oviposisi nyamuk Culex quinquefasciatus berdasarkan isyarat warna yang terhasil daripada ekstrak tumbuhan Ipomoea cairica. Dalam kajian ini, dua kumpulan eksperimen untuk pilihan oviposisi telah dijalankan: (1) satu konsentrasi larutan di dalam satu sangkar; dan (2) pelbagai konsentrasi larutan di dalam satu sangkar. Dalam kajian satu konsentrasi larutan, terdapat cuma satu sahaja tempat oviposisi yang disediakan dan ditawarkan kepada lima nyamuk betina gravid. Manakala dalam kajian pelbagai konsentrasi larutan, 4 tempat oviposisi disediakan dan ditawarkan kepada 20 betina gravid. Konsentrasi yang diuji pada 100 mL adalah: (1) kawalan (air suling sahaja); (2) 50 ppm, (3) 150 ppm; dan (4) 300 ppm ekstrak tumbuhan I. cairica. Konsentrasi tertinggi pada 300 ppm menunjukkan intensiti tertinggi dengan warna tergelap diikuti dengan konsentrasi 150 ppm dan 50 ppm. Lebih banyak betina gravid didapati lemas dalam konsentrasi tertinggi iaitu 300 ppm berbanding 150 ppm dan 50 ppm ekstrak yang diuji. Tiada telur dijumpai dalam semua konsentrasi. Ekstrak yang dikaji didapati berkesan untuk menarik nyamuk Cx. quinquefasciatus betina gravid untuk bertelur dan seterusnya menyebabkan kematiannya dan menghalang aktiviti peneluran. Gangguan yang disebabkan oleh ekstrak aseton I. cairica terhadap aktiviti oviposisi Cx. quinquefasciatus akan memberikan kesan kawalan yang lebih baik kepada serangga vektor.